The Family as a Space for Religious Spiritual Formation: A Study of the Concept of Ecclesia Domestica - Nurhayati Mega Putri Tumanggor; Tri Chandra Fajariyanto (Universitas Islam Negeri Sumatera Utara, 2026)
This research seeks to illustrate how Catholic families live out their faith as Ecclesia Domestica in both their everyday existence and in their church involvement at the Sitinjak Temba Station. The methodology employed is a qualitative descriptive approach, which includes eight participants comprising parents, children, and members of the church leadership. Information was gathered through methods such as direct observation, extensive interviews, and documentation, which were then analyzed via the Miles and Huberman interactive model. Results reveal that Catholic families demonstrate their beliefs through various religious practices at home, nurturing their children's spirituality, employing religious symbols, and integrating Christian principles into their daily activities. Furthermore, the family's faith is shown through their active engagement in the Church's mission, especially in the areas of liturgy, kerygma, koinonia, diakonia, and martyria. These results suggest that families serve not just as recipients of pastoral support, but as engaged participants in the Church’s life and mission. Consequently, Catholic families at the Sitinjak Temba Station have worked diligently to embody their identity as Ecclesia Domestica in both family and church contexts.